FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU HIDUP BERSIH DAN SEHAT DI TATANAN RUMAH TANGGA KABUPATEN MUARO JAMBI - Sri Rukaiyah (Sekolah Tinggi Pariwisata Mataram, 2022)
A person's healthy condition can be achieved by changing unhealthy behavior into healthy behavior and creating a healthy environment. the application of clean and healthy living behavior (phbs) in household settings is one of the strategic efforts to mobilize and empower to live clean and healthy behaviors. this study aims to determine the factors associated with clean and healthy living behavior in household settings. this research is aquantitative research with a cross sectional approach. the research sample was households in the bird's nest village with a total sample of 65 people. the sampling technique used was purposive sampling technique. the research instrument is a questionnaire. data collection techniques with interviews. data were analyzed using chi square statistical test. the results of univariate analysis showed that 76.9% of respondents had good clean and healthy behavior, 53.8% of respondents had good knowledge and 52.3% of respondents had good attitudes. the results of the bivariate analysis showed that there was no relationship between knowledge (p=0,352) and attitudes (p=0,167) with clean and healthy living behavior in household settings. based on this, it can be concluded that clean and healthy living behavior in household settings in bird's nest village is not related to knowledge and attitudes.